The Role of optimism in students’ psychological well-being - fadilah, nayla alyatil (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the contribution of optimism to students’ psychological well-being. University students are in a developmental stage characterized by the transition from late adolescence to early adulthood, a period often accompanied by various academic, social, and emotional demands. Such challenges frequently create psychological pressure that may negatively affect students’ overall well-being if not managed effectively. In this context, optimism is considered an important psychological resource that can assist students in dealing with challenges encountered during academic life. An optimistic perspective enables individuals to maintain positive expectations for the future and remain confident in overcoming obstacles despite difficult circumstances. This research employs a qualitative approach using a library research method. Data and information were gathered from various relevant academic sources, including scholarly journals, books, and previous studies related to the topic under discussion. These references were analyzed comprehensively to gain a deeper understanding of the relationship between optimism and students’ psychological well-being. The findings indicate a positive association between optimism and students’ psychological well-being. Students who possess a higher level of optimism tend to be more resilient when facing stress, demonstrate stronger adaptability, and are less likely to give up when confronted with challenges. Furthermore, having a constructive outlook on the future encourages individuals to persist in seeking solutions to problems they encounter.